Applying Learning by Teaching Strategy in Learning TOEFL: Strength and Weaknesses - Ratri Nur Hidayati; Arilia Triyoga; Fitri Merawati (Borneo Educational Journal (Borju), 2023)
This research is aiming at revealing the strength and weaknesses of applying learning by teaching strategy in learning TOEFL. Since TOEFL is regarded as a challenging English proficiency test, the students need to find the suitable strategy in mastering TOEFL. This research belongs to survey research. It utilizes descriptive qualitative data analysis. Several steps were taken in this study, namely: designing survey, writing questions, designing sample, conducting the survey, analyzing the data. Then, the instruments used in this research were questionnaires. The data were analyzed descriptively. Based on search result, the strength of applying learning by teaching strategy are: (1) easiness, (2) practice public speaking, (3) peer-correction, (4) responsible, (5) independent. While the weaknesses are: (1) pronunciation, (2) classroom management, (3) psychological problem, (4) difficulties in transferring the material.